Strengthening RC beams with mid-span supporting prestressed CFRP plates: An experimental investigation. (1st December 2022) - Yang, Jia-Qi; Feng, Peng; Liu, Bin; Wang, Husheng; Zhao, Weiping; Hu, Lili
Highlights: Novel prestressing method strengthening of RC beams with prestressed CFRP plate. Full range load–deflection-stress behaviour of prestressed beam. Achieving pseudoplastic structural behaviour using CFRP materials. Abstract: This paper proposes a novel strengthening method for reinforced concrete (RC) beams using prestressed carbon fibre-reinforced polymer (CFRP) plates. In the proposed method, the CFRP plate is stressed by adjusting the position of the mid-span deviators. The strengthening process is fast and easy to apply because there is no need for hydraulic jacks or adhesives. To investigate the behaviour of the strengthened RC beams, a series of tests were conducted on both intact and damaged beams with different strengthening configurations, and the full range behaviours of the beams are reported in detail. According to the test results, the maximum stress of the CFRP plate reached 1500 MPa, and the beam strength was enhanced up to 43%. Some of the strengthening schemes achieved good ductility. As a result, the proposed strengthening method is found to be effective and can be further developed into a pseudoplastic CFRP strengthening system.